Previsão climática sazonal do regime térmico e hidrodinâmico de reservatório - Lemos, Wictor Edney Dajtenko (2015)
The dynamics of water quality related processes in reservoirs is a function of its morphology, the action of meteorological variables and defluências inflows and, to a greater extent. Predict the hydrodynamic behavior of reservoirs and the impact of changes or variability in weather forcing is essential to the management of water quality and was the main objective of this thesis. Therefore, we used climate models, hydrological, hydrodynamic and energy balance in cascade. The behavior of the resulting hydrodynamic modeling showed results in line with tropical reservoirs, representing the daily patterns of movement and the formation of thermal stratification in modeled reservoir. The main hydrodynamic seasonal variations could be modeled, albeit with a high level of uncertainty. Monitoring on a Miranda Pereira reservoir that provided a means to begin the modeling and integrated monitoring cycle was performed. The dynamic downscaling technique to obtain the meteorological variables of regionalized forecast was presented, showing some application possibilities of the results of climate models in hydrodynamic modeling of reservoirs, essential in modeling of water quality. The results showed the possibility of calibration and validation of the hydrodynamic model CE-QUAL-W2 using atmospheric reanalysis data, application of climate prediction techniques in assessing and predicting the hydrodynamic patterns of tanks and the need for a monitoring system as Subsidiary information relevant to modeling, to improve existing systems and increase the level of knowledge about the dynamics of reservoirs located in the semiarid